Development of a two-variable linear inequality system mathematics learning design with a problem-based learning model - Simbolon, Rotua; Hakim, Lukman El; Aziz, Tian Abdul; Aurelia, Flavia (Desimal: Jurnal Matematika, 2023)
Teachers are designers, implementers, and evaluators of learning. The teacher's ability to design learning that favors students will greatly affect the quality of the learning process and the learning outcomes that will then be obtained by students. This study aims to develop a problem-based learning design for the more interesting topic of systems of two-variable linear inequalities. This development research uses the Dick & Carey development model. The Dick & Carey model can be an alternative for teachers in designing pro-student learning because, by design, this model starts with student and context analysis as well as instructional analysis, which will provide sufficient information and evidence about the characteristics and needs of students as well as instructional objectives that are appropriate to the level of their education and stage of development.